(untitled) (Eurasian Research Bulletin, 2023)
This article describes the spiritual mentoring of Alisher Navoi Nadira begim. Navoi was the great thinker of his time, a master of words. The ghazals of Nadira contained the figure of Navoi, which the ghazals wrote about, comparing with his works. The role of Alisher Navoi in the creative formation of the poet is undeniable. Nadira (Mohlaraim) analyzed on the examples the features in the work of Alisher Navoi, also found in her work. In Eastern literature, examples were given of the legacy. In that case, Nadirabegim (Mohlarayim) left to her ancestors, known to the people for her abilities and wisdom, continuing the noble work of her ancestors on the way to science, enlightenment and prosperity of the country, that the works created by her hade not lost their educational value either in space or in time. Nadirabegim commented on an Uzbek woman who created an exemplary school for Uzbek women.